CONSTITUTIONAL RIGHT TO COMPLAIN AS A FORM OF DEMOCRACY - Borodin, Ivan; Vodolaskova, Kateryna (Proceedings of National Aviation University (archive), 2018)
In the article in the process of substantiation such basic components of the constitutional right of citizens to complain (as forms of manifestation of democracy) as legal and social content are indicated; as well as its functions; which are law enforcement; social control; the ability to express their own opinion on a particular issue. The aim and objectives of research. Article 3 of Constitution of Ukraine states that human; his life and health; honor and dignity; inviolability and security are recognized in Ukraine as the highest social value. Human rights and freedoms determine the content and direction of state activity. This means that the personality of a human is a value not only for himself but for the whole society. The Constitution and the rights and freedoms of human and citizen are a manifestation of democracy in Ukraine. The purpose of this article is an attempt to point out the basic directions of solving problems of the constitutional right to complain as a form of expression of such form of democracy. Materials and research methods: comparative legal; sociological; historical; logical; dialectical. Results: the analysis shows; that the current legislation; while establishing the right of citizens to a complaint; provides different legal regimes for its securement; knowledge and understanding of which will enable to implement this constitutional right in practice. Discussion: In this article; the authors propose to discuss the main issuues on the problems of general and special complaint; criteria for their differentiation.